IMPROVING STUDENTS’ ABILITY IN ENGLISH VOCABULARY MASTERY BY USINGPICTURE AND PICTURE STRATEGY AT THE SEVENTH GRADE OF SMP SWASTA HOYA SEJAHTERA IN 2018/2019 ACADEMIC YEAR - Lase, Arisman (Universitas Nias Raya, 2022)
This research is aimed at improving students’ ability in mastering vocabulary through the implementation of Picture and Picture Strategy. This research took the seventh grade students of SMP Swasta Hoya Sejahtera as the subject of the research which consisted of 26 students. This research was designed using CAR method that involved planning, action, observation, and reflection. There were two cycles done. The teaching material chosen were ‘describing parts of human body’ and ‘describing peoples’ activities for everyday’. Instruments of data collection were observation papers as qualitative data and the test as quantitative data. Qualitative data wasanalysed bySudjono (2014:82-83). Data analysis result shows that students’ ability in mastery vocabulary was significantly improved by implementation of Picture and Picture Strategy.Based on the observation papers, result it shows that activities done were increased each meeting. In addition, the test result in cycle I shows that there were 53.76 students who passed MCC by average score was 61.53. This achievement was significantly improved in cycle II to 92.16% who passed MCC by average score was 82. Total improvement from before conducting research to cycle II was 61.44%. It is concluded that this research was successfully implemented and Picture and Picture strategy is effective to improve students’ ability in mastering vocabulary. It is recommended that this teaching strategy to be implemented to another related skills.